Sectoral Productivity Gaps and Aggregate Productivity - Sinha, Rishabh (World Bank E-Library Archive, 2016)
This paper examines the role of changes in sectoral productivity gaps over time in accounting for growth realized by countries over the past few decades. To quantify the productivity impact of the sectoral gaps, a simple model of resource allocation is developed in which the gaps arise due to distortions in the form of asymmetrical taxes across sectors. The paper finds a limited role of changes in distortions over time in accounting for actual growth. Implied growth from changes in distortions accounts for less than 2.5 percent of actual growth for the median country. To check if the lower contribution of changes in distortions is because of unrealized gains suggested by high levels of present distortions, productivity gains are estimated when distortions across countries are reduced to the US levels. Barring a couple of cases, the gains in aggregate productivity are modest across the sample of countries